THE PREPARATION OF INSTRUCTIONAL MEDIA IN TEACHING ENGLISH TO YOUNG LEARNERS AT SDN BAROS MANDIRI 3 CIMAHI - Silfia Ayuningtias; Evie Kareviati (IKIP Siliwangi, 2021)
This study has two purposes, the first is describing how the teacher’s preparation the instructional media and the second one is explaining how the teacher’s utilized the instructional media in teaching English to young learners. This study was conducted in SDN Baros Mandiri 3 Cimahi at fifth-grade students. To collect the data the researcher used observation in the classroom and interview with the English teacher. This method used a descriptive qualitative. The result of this study showed that in preparing the instructional media the teacher did two kinds of preparation. The English teacher’s stated that the preparation was: first, selecting the suitable instructional media related to the material that will be taught. Second, mastering the material for delivering to students. The instructional media used by the English teacher’s is flashcards, the English teacher’s stated that flashcards are mostly because it doesn’t need a lot of preparation. Flashcards are also useful to help the teacher in the learning process because the students can visualize the words through seen at the flashcards. The use of flashcards also easy, the teacher only needs to show one by one of the pictures to all students and they would be guessed the name of the pictures related to the material, students who can guess will come to the front of the class and write down the word in English.